AFOLAYAN, Adeshina, Olajumoke, YACOB-HALISO and Toyin FALOLA (eds). Pentecostalism and Politics in Africa: African Histories and Modernities. (9th September 2020) - Heuser, Andreas
Abstract : AFOLAYAN, Adeshina, Olajumoke, YACOB-HALISO and Toyin FALOLA (eds). Pentecostalism and Politics in Africa: African Histories and Modernities. Cham, Switzerland: Palgrave Macmillan, 2018. 452pp. Pbk. ISBN 9783319749112. €83.